Legacy of the Czar: Complementarity between education and work in Russia - Aigerim Zhangaliyeva; Masaki Nakabayashi (Journal of Applied Economics, 2023)
Vocational school graduates enjoy a higher employment probability than other types of graduates across industrial economies. This may result from either the signaling effects of vocational school degrees or skill complementarity between vocational schooling and work experience. Regarding wage regressions, signaling effects should make the coefficient of the interaction term between years of schooling and work experience negative, whereas complementarity between education and work experience should increase this coefficient because the cross-derivative of output with respect to schooling and work experience is positive. Thus, the negativity of the interaction term between years of schooling and work experience decreases as schooling becomes more complementary to work. We find that the negativity of the interaction term is smaller for vocational track graduates than for general track graduates in Russia. This result is arguably because the Russian vocational track emphasizes complementarity between education and work to a greater degree than its general track.
Keywords: 330; employer learning; European stratified education system; schooling/experience complementarity; vocational education